Incidence Trends of Type 1 and Type 2 Diabetes among Youths, 2002–2012 - Mayer-Davis, Elizabeth J; Lawrence, Jean M; Dabelea, Dana; Divers, Jasmin; Isom, Scott; Dolan, Lawrence; Imperatore, Giuseppina; Linder, Barbara; Marcovina, Santica; Pettitt, David J; Pihoker, Catherine; Saydah, Sharon; et al. (The New England journal of medicine, 2017)
This study ascertained cases of type 1 and type 2 diabetes among youths from 2002 through 2012 at five U.S. study centers. After adjustment for age, sex, and race or ethnic group, there were relative annual increases in the incidences of type 1 and type 2 diabetes. Diagnoses of type 1 and type 2 diabetes in youths present a substantial clinical and public health burden owing to the challenges of disease management and the risks of acute and chronic complications. 1 The SEARCH for Diabetes in Youth study (hereafter, the SEARCH study) previously showed increases in the prevalences of both diseases in the 2001–2009 period. 2 However, data on the trends in incidence are needed to understand the current and potential burden of diabetes more fully. Previous reports have shown that the incidence of type 1 diabetes has increased worldwide over the past three decades. 3 – 8 Data from Australia . . .